TREATMENT OF PATIENTS WITH ESSENTIAL HYPERTENSION 1-2 GRADE WITH METOPROLOL TARTRATE AND ANALYSIS OF HEART RATE VARIABILITY - V. E. Oleinikov; V. A. Budanova; A. V. Kulyutsin (Столичная издательская компания, 2015)
Aim. Optimization of therapy in patients with arterial hypertension (HT) 1-2 grade considering heart rate variability (HRV) and efficacy of metoprolol tartrate in long-acting presentation (Egilok retard) during 96 weeks of usage. Material and methods. 33 patients with mild to moderate HT were treated with Egilok retard. Doses were titrated from 50 to 200mg\daily. If the target level of blood pressure (BP) wasn't reached, hydrochlorothiazide (12,5-25 mg\daily) was added. Ambulatory BP and ECG monitoring with HRV analysis were carried out before start and after 24, 48, 96 weeks of therapy, echocardiography - after 48 and 96 weeks. Life quality was estimated by four-grade scale. Results. After 96 weeks 20 patients continued this therapy (60, 6%). Monotherapy provided of BP target level in 13 patients (65%), combined therapy - in 7 (35%). The high patient compliance to the treatment was based on considerable and stable antihypertensive effect, absence of side effects and improvement of life quality during 96 weeks as well as consideration of HRV type. It was suggested to split patients in groups with high, normal and low levels of HRV. It was mostly difficult to reach BP targets in patients with low HRV level. They took combined therapy in 62% (p>0,005). 7 patients demonstrated normalization of disturbed diastolic function which means heart remodelling regress. The longer therapy with Egilok retard showed more significant cardioprotective effect. Conclusion. Long-term therapy with Egilok retard provides improvement of life quality and significant cardioprotective effect. Beta-blocker therapy can be optimized by consideration of HRV patient type.